2020
DOI: 10.1242/jeb.232645
|View full text |Cite
|
Sign up to set email alerts
|

The phase shift between potential and kinetic energy in human walking

Abstract: It is known that mechanical work to sustain walking is reduced thanks to a transfer of gravitational potential energy into kinetic energy as in a pendulum. The factors affecting this transfer are unclear. In particular it is not known the phase relationship between potential and kinetic energy curves of the center of mass. This relationship has been measured in this study. The normalized time intervals: i) α, between maximum of kinetic energy in the sagittal plane Ek and minimum of gravitational potential ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 13 publications
3
19
0
Order By: Relevance
“…With respect to NW, the times were approximately equal in the Parkinson group with trends of symmetry only at 1.8 km h −1 . This is in line with a previous study that reported similar times in healthy males during FW at the most common speed, 12 resulting in a higher pendulum‐like recovery during NW than in FW.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…With respect to NW, the times were approximately equal in the Parkinson group with trends of symmetry only at 1.8 km h −1 . This is in line with a previous study that reported similar times in healthy males during FW at the most common speed, 12 resulting in a higher pendulum‐like recovery during NW than in FW.…”
Section: Discussionsupporting
confidence: 93%
“…In healthy males during FW, the upward and downward displacements are symmetrical at their self-selected walking speed (~5.8 km h −1 ) reaching greater recovery energy, and the times become asymmetrical in speeds below 3.2 km h −1 and above 6.8 km h −1 . 12 With respect to NW, the times were approximately equal in the Parkinson group with trends of symmetry only at 1.8 km h −1 . This is in line with a previous study that reported similar times in healthy males during FW at the most common speed, 12 resulting in a higher pendulum-like recovery during NW than in FW.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations